Stress-induced diabetic ketoacidosis in concurrent ectopic pregnancy: A case report - Adam D. Elwood; Neeti Misra (Elsevier, 2023)
Ectopic pregnancy occurs in 1-2% of all pregnancies. The majority occur in the fallopian tube, requiring intervention in the form of methotrexate or surgery. Ruptured ectopic pregnancies can lead to hemodynamic instability, requiring immediate surgical intervention. In the case reported here, the patient presented in diabetic ketoacidosis with a pregnancy of unknown location. Upon further evaluation she was found to have a ruptured ectopic pregnancy and was taken to the operating room for surgical management. We discuss the rarity of these concurrent disorders, the pathophysiology behind stress-induced diabetic ketoacidosis, the effects of elevated glucose in peri-operative management, and the importance of multi-disciplinary approaches to urgent clinical decision-making.